High interface compatibility and phase change enthalpy of heat storage wood plastic composites as bio-based building materials for energy saving. (July 2022) - Zhao, Junqi; Li, Yanchen; Fang, Xiaoyang; Sun, Jingmeng; Zhang, Weiye; Wang, Beibei; Xu, Jianuo; Liu, Yi; Guo, Hongwu
Abstract: Phase change materials (PCMs) is one of the most efficient and reliable methods to store latent heat and reduce energy consumption. This work focused on heat-storage bio-based building materials for energy-saving using encapsulate poly (ethylene glycol) (PEG)/organic diatomite (O-Dt) as the latent heat storage agents, and wood fiber (WF)/high-density polyethylene (HDPE) as the matrix. PEG was encapsulated into the porous structure of Dt, and the obtained form-stable PCM has desired great interface action, high latent heat (105.35 J/g), good packaging capability, and excellent thermal stability. The heat-storage WPCs incorporated with form-stable PCM possessed considerable thermal storage capacity (60.42 J/g) and temperature-regulating ability (12 °C–15 °C). The thermal conductivity of WPC-20% was increased by 26.7% than WPC-0%. The mechanical strength and hydrophobicity of WPCs were increased when the loading percentage of PCM was 5%. Thermal cycling test results demonstrated that the heat storage WPCs had considerable heat storage reliability and chemical stability. The satisfying latent heat capacity and acceptable mechanical strength indicated the heat-storage WPCs could be potentially utilized as building materials for low carbon and energy conservation. Highlights: Provide a novel WPCs for reducing building energy consumption. Investigate the interface of form-stable PCMs and heat-storage WPCs. The form-stable PCMs and heat-storage WPCs had efficient temperature-regulated ability. Analyzed the hydrophobicity, mechanical properties of heat-storage WPCs.